UMPSA Confucius Institute hosts international conference - Nor Salwana, Mohammad Idris (UMPSA, 2023)
PEKAN, 2 November 2023 – Nearly 50 lecturers and educators from across the country participated in the 2023 Malaysia Confucius Institute Conference and International Chinese Teachers Sharing Forum organized by Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) at the Banquet Hall of UMPSA Pekan.